Discharges With Triphasic Morphology as Marker of the Risk of Death in Acute Encephalopathy. (March 2022) - Merchán-del-Hierro, Xavier; Persi, Gabriel; Vulycher, María C.; Chicco, Carla; Gatto, Emilia M.; Pereira-de-Silva, Nahuel
Introduction . In clinical practice, it is difficult to define the prognosis of patients with acute encephalopathy; a syndrome characterized by cognitive dysfunction and altered sensorium. Discharges with triphasic morphology (DTM) are an electroencephalographic pattern that might be useful to establish the risk of death. The aim of this study was to define the prognostic value of DTM regarding mortality in patients with acute encephalopathy. Methods . We conducted an observational retrospective cohort study including patients with acute encephalopathy with and without DTM paired by age and gender in a 1:2 ratio. We calculated the odds ratio (OR) to determine the association between DTM and mortality. In addition, we calculated sensibility, specificity, and predictive values. Results . We included 72 patients, 24 with DTM and 48 without DTM. Mortality was higher in patients with DTM (41.6% vs 14.5%, P = .01). Factors associated with a higher risk of death were DTM (OR = 4.1, 95% confidence interval [CI] 1.3-13, P = .01) and sequential organ failure assessment score (OR = 1.3, 95% CI 1.04-1.67, P = .02). A higher Glasgow coma scale score was associated with a lower risk of death (OR = 0.65, 95% CI 0.51-0.83, P = .001). The sensibility and specificity of DTM were 59% and 75%, respectively. Positive and negative likelihood ratios were 2.36 and 0.55. Discussion . Our results revealed high mortality in patients with acute encephalopathy and DTM. This electroencephalographic pattern was associated with 4 times higher risk of death. However, its usefulness for predicting death was limited.